Navajo - Bird, F. A. (Minneapolis, Minnesota : Checkerboard Library, an imprint of Abdo Publishing, 2022)
This book introduces young readers to the Navajo people, their traditional ways of life, including social structure, homes, food, art, clothing and more, their contact with Europeans, and how the Navajo are keeping their culture alive today.
Homelands -- Society -- Homes -- Food -- Clothing -- Crafts -- Family -- Children -- Medicine people -- War -- Contact with Europeans -- Barboncito -- The Navajo today.
Includes index.
5.3
3-6
790L
Keywords: Navajo Indians -- Juvenile literature; Indigenous peoples -- Social life and customs -- Juvenile literature; Ethnology -- Juvenile literature; Navajo Indians; Indigenous peoples -- Social life and customs; Ethnology; Indians of North America